Extending the mechanical-durability performance of hot mix asphalt modified with waste aluminum scrape powder - Al-Obaidi, Mahmood; Abed , Alaa H. (Al-Nahrain Journal for Engineering Sciences, 2026)
Moisture damage in terms of stripping; and aging surface in terms of raveling and abrasion are among the primary distresses that lead to the deterioration of asphalt pavement, diminishing the overall quality and functionality of road surfaces. This study investigates the impact of using low-cost and locally available waste aluminum scrape powder (WASP) with a particle size ranging from sieves No.8 to No.200. WASP exhibits a high bulk specific gravity and melting point temperature on HMA mixtures, which could also potentially enhance the density and stiffness of modified mixtures. Five quantities of additives 0.5, 1.0, 1.5, 2.0, and 2.5% have been used to enhance the mechanical-durability features. The aggregate sources of AlDoz and AlNibaa'e were chosen, and different mixtures were produced utilizing Marshall and Roller compaction methods. The study's findings indicated that WASP enhanced mechanical-durability characteristics and reduced the asphalt mixture's sensitivity to abrasion, moisture damage, and aging. The optimal amount of WASP was determined to be 1.5%. In addition, based on the influence of the aggregate source and compaction technique, it is visible that the AlNibaa'e source and roller compaction mode provide superior outcomes compared to the AlDoz aggregate source and the Marshall method.